The effect of attachment style on entrepreneurial behavior: personal accomplishment as a moderator - Gülçin Kazan; Tuğçe Uzun Kocamış (BMC Psychology)
Abstract Entrepreneurs are the primary drivers of economic growth in a globalizing world, and as such, it is imperative to understand the psychological determinants of entrepreneurial activity. Even though existing studies have examined some personal traits that influence entrepreneurial behaviors, the exact interplay between attachment styles and entrepreneurial tendencies among students at the university level has not been exhaustively studied [1–2]. Moreover, the potential moderating effect of personal sense of accomplishment is overlooked. This study aims to fill this gap by investigating the effects of attachment styles on entrepreneurial behaviors and the moderating role of personal sense of accomplishment using a sample of 411 Istanbul university students. The study reveals that entrepreneurs with secure attachment styles are more likely to have entrepreneurial intentions, and a high sense of personal accomplishment significantly contributes to such intentions. Such findings suggest that support initiatives and entrepreneurship education should place a very high priority on the acquisition of a sense of personal accomplishment to enable entrepreneurial action.